KONSEP PEMBENTUKAN KEPUTUSAN DALAM AKUISISI SISTEM INFORMASI AKUNTANSI: SEBUAH PERSPEKTIF TEORI SCHEMATA - Syarifuddin Syarifuddin (AkMen JURNAL ILMIAH, 2016)
Trust is the determining factor in selection decisions about technology. On the theory of technology acceptance (TAM), the theory of planning behavior (TPB), social cognitive theory (CST) and the unified theory and adoption of used technology (UTAUT) the trust factor is less elaborated in relation to the formation of attitudes in technology selection. The author proposes the theory of schemes, one of social cognitive theory to study the formation of trust in individual cognition that support decision making in the selection of individual decision information technology systems. This article aims to develop a scheme theory literature, especially in relation to the adoption of accounting information systems technology. While providing a better knowledge on the part of the marketing information system technology in marketing technology products, especially related to the factors forming the individual's belief in choosing a technology product. Understanding of the factors and sources of trust also provide direction for the company in managing long-term business relationships with its customers.